2015
DOI: 10.3389/fpsyt.2015.00095
|View full text |Cite
|
Sign up to set email alerts
|

Tourette Syndrome: Complementary Insights from Measures of Cognitive Control, Eyeblink Rate, and Pupil Diameter

Abstract: Some individuals with Tourette syndrome (TS) have severe motoric and vocal tics that interfere with all aspects of their lives, while others have mild tics that pose few problems. We hypothesize that observed tic severity reflects a combination of factors, including the degree to which dopaminergic (DA) and/or noradrenergic (NE) neurotransmitter systems have been affected by the disorder, and the degree to which the child can exert cognitive control to suppress unwanted tics. To explore these hypotheses, we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Two studies examined motor control. In a clever analysis of video recordings of the eyes 55 , spontaneous blink rate, which is related to dopamine levels, was higher in children with TS than in controls both during task performance and during a rest period. In contrast, pupil diameter, which is related to norepinephrine levels, was correlated with anxiety in TS subjects although not in controls.…”
Section: Resultsmentioning
confidence: 93%
“…Two studies examined motor control. In a clever analysis of video recordings of the eyes 55 , spontaneous blink rate, which is related to dopamine levels, was higher in children with TS than in controls both during task performance and during a rest period. In contrast, pupil diameter, which is related to norepinephrine levels, was correlated with anxiety in TS subjects although not in controls.…”
Section: Resultsmentioning
confidence: 93%
“…Previous investigations have examined the resting blink rate in TS at rest or during various tasks. Some found an increased spontaneous blink rate in TS (Bonnet 1982; Tulen et al, 1999; Tharp et al, 2015), whereas another did not (Karson et al, 1985). Nevertheless, we show decreased suppression of the blink rate in TS during intentional suppression.…”
Section: Discussionmentioning
confidence: 98%
“…In Simon tasks, normal performance is often reported in both children [ 174 , 175 , 176 ] and adults [ 122 , 123 ]. However, impaired Simon task performance has also been found in children [ 177 ] and adults [ 178 ] with TS. In their study, Tharp et al [ 177 ] reported that tic severity was negatively correlated with accuracy and positively with response time (RT).…”
Section: A Review Of Neuropsychological Functioning In Tsmentioning
confidence: 99%
“…However, impaired Simon task performance has also been found in children [ 177 ] and adults [ 178 ] with TS. In their study, Tharp et al [ 177 ] reported that tic severity was negatively correlated with accuracy and positively with response time (RT). Such correlation between RT and tic severity was also reported in the study of Baym et al [ 175 ], suggesting that while TS patients’ performance in this type of task is usually intact [ 130 ], patients with severe tics could experience some difficulty.…”
Section: A Review Of Neuropsychological Functioning In Tsmentioning
confidence: 99%